2022
DOI: 10.1111/acv.12771
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale, multivariate community models improve designation of biodiversity hotspots in the Sunda Islands

Abstract: Species occur in sympatric assemblages, bound together by ecological relationships and interspecific interactions. Borneo and Sumatra host some of the richest assemblages of biota worldwide. The region, however, faces the highest global deforestation rates, which seriously threaten its unique biodiversity. We used a large camera trap dataset that recorded data for 70 terrestrial species of mammals and birds, to explore the drivers of regional species richness patterns. Using a multi-scale, multivariate modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 74 publications
3
12
1
Order By: Relevance
“…Indonesian Academic of Science (LIPI) also reported that around 70% of endangered species occurred outside the protected areas [ 101 ]. A previous study also showed that less than 20% of biodiversity hotspots occurred within protected areas in Sumatra [ 102 ]. However, they may be more vulnerable than previously thought if they are not utilizing protected areas for protection.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesian Academic of Science (LIPI) also reported that around 70% of endangered species occurred outside the protected areas [ 101 ]. A previous study also showed that less than 20% of biodiversity hotspots occurred within protected areas in Sumatra [ 102 ]. However, they may be more vulnerable than previously thought if they are not utilizing protected areas for protection.…”
Section: Discussionmentioning
confidence: 99%
“…Before this study, no comprehensive survey had taken place since 1985, impeding assessment of the reserve's effectiveness, which is a general problem in the management of protected areas [71]. Chiaverini et al [72] used camera-trap data to extrapolate the distributions of vertebrate species richness across Borneo and Sumatra and found that high species richness areas did not correlate well with the International Union for Conservation of Nature range maps, which are based on historical distribution data (https://www.iucnredlist.org, accessed 18 April 2022). Finally, Hamilton et al [3] compiled decades of standardized biodiversity inventory data for 2216 species in the continental USA and interpolated to identify areas of unprotected biodiversity importance (using a measure similar to site irreplaceability, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Before this study, no comprehensive survey had taken place since 1985, impeding assessment of the reserve’s effectiveness, which is a general problem in the management of protected areas (Maxwell et al, 2020). Chiaverini et al (2022) used camera-trap data to extrapolate the distributions of vertebrate species richness across Borneo and Sumatra and found that high species richness areas did not correlate well with IUCN range maps, which are based on historical distribution data (https://www.iucnredlist.org, accessed 18 April 2022). Finally, Hamilton et al (2022) compiled decades of standardized biodiversity inventory data for 2216 species in the United States and extrapolated across the country (excluding Alaska and Hawaii) to identify areas of unprotected biodiversity importance (using a measure similar in spirit to site irreplaceability, i.e.…”
Section: Discussionmentioning
confidence: 99%